Adequacy of Immersive Virtual Reality for the Perception of Daylit Spaces: Comparison of Real and Virtual Environments. Issue 2 (3rd July 2019) - Chamilothori, Kynthia; Wienold, Jan; Andersen, Marilyne
ABSTRACT: This article presents a novel experimental method that uses a virtual reality (VR) headset, aiming to provide an alternative environment for the conduction of subjective assessments of daylit spaces. This method can overcome the difficulty of controlling the variation of luminous conditions, one of the main challenges in experimental studies using daylight, and its novelty lies in the implementation of physically based renderings into an immersive virtual environment. The present work investigates the adequacy of the proposed method to evaluate five aspects of subjective perception of daylit spaces: the perceived pleasantness, interest, excitement, complexity, and satisfaction with the amount of view in the space. To this end, experiments with 29 participants were conducted to compare users' perceptions of a real daylit environment and its equivalent representation in VR and test the effect of the display method on the participants' perceptual evaluations, reported physical symptoms, and perceived presence in the virtual space. The results indicate a high level of perceptual accuracy, showing no significant differences between the real and virtual environments on the studied evaluations. In addition, there was a high level of perceived presence in the virtual environment and no significant effects on the participants' physical symptoms after the use of the VR headset. Following these findings, the presented experimental method in VR seems very promising for use as a surrogate to real environments in investigating the aforementioned five dimensions of perception in daylit spaces.